A Low Complexity Algorithm for Direction of Arrival Estimation With Direction-Dependent Mutual Coupling - Ge, Qichao; Zhang, Yongshun; Wang, Yizhe (IEEE communications letters, 2020)
In this letter, a novel low complexity algorithm with two variants is proposed for improving the efficiency of direction of arrival (DOA) estimation with direction-dependent mutual coupling. In uniform linear array, the special structure of mutual coupling matrix (MCM), which is a banded symmetric Toeplitz matrix, is exploited in the proposed method. A new transformation is constructed using the structural characteristics of the MCM, and two spectral functions are constructed via the orthogonality of the transformed matrix and the noise subspace. Finally, the two spectral functions are utilized to obtain the DOAs of sources by searching spectrum peaks. The proposed method avoids estimating multiple mutual coupling coefficients and iteratively solving convex optimization problem. The validity and superiority of the novel algorithm in conditions of direction-dependent mutual coupling is demonstrated in the simulations.